EFEK SQUAT EXERCISE PADA UNTUK MENGURANGI GRADE SELULIT PADA WANITA (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2018)
Objective: To know effects of addition Exesice Squat to Reduce Grade cellulite in women. Methods: sample was selected based purposive sampling, Ankle functional is measured using Foot function index. Samples based on Pocock formula consist of 10 people. Treatment Group with Squat exercise. Result: Normality test with shapiro wilk test obtained not normal diffusion data, homogenity test with Levene's test got homogenous data. The result of hypothesis test on treatment Wilcoxon sign rank test obtained value p= 0.034. Conclusion: there is effect of adding squat exercise to decrease grade cellulite in women Â Keywords: squat exercise, Laser, decrease grade cellulite